Adaptive radiation in labrid fishes: A central role for functional innovations during 65 My of relentless diversification. (1st February 2019) - Burress, Edward D.; Wainwright, Peter C.
Abstract: Early burst patterns of diversification have become closely linked with concepts of adaptive radiation, reflecting interest in the role of ecological opportunity in modulating diversification. But, this model has not been widely explored on coral reefs, where biodiversity is exceptional, but many lineages have high dispersal capabilities and a pan‐tropical distribution. We analyze adaptive radiation in labrid fishes, arguably the most ecologically dominant and diverse radiation of fishes on coral reefs. We test for time‐dependent speciation, trophic diversification, and origination of 15 functional innovations, and early bursts in a series of functional morphological traits associated with feeding and locomotion. We find no evidence of time‐dependent or early burst evolution. Instead, the pace of speciation, ecological diversification, and trait evolution has been relatively constant. The origination of functional innovations has slowed over time, although few arose early. The labrid radiation seems to have occurred in response to extensive and still increasing ecological opportunity, but within a rich community of antagonists that may have prevented abrupt diversification. Labrid diversification is closely tied to a series of substantial functional innovations that individually broadened ecological diversity, ultimately allowing them to invade virtually every trophic niche held by fishes on coral reefs.